Implementasi Spasial Algoritma Harvesine pada Mapbox API Untuk Pemetaan Pariwisata - Ahmat Adil; Bambang Krismono Triwijoyo (Jurnal Bumigora Information Technology (BITe), 2023)
Background: Lombok is one of the tourist destinations in West Nusa Tenggara (NTB) Province, which has various kinds of tourist destinations. Before the Covid 19 pandemic, the number of tourist visits to NTB, especially the island of Lombok, increased every year.Objective: This study aimed to implement the haversine algorithm in finding and determining the closest route to tourist destinations on Lombok Island to make it easier for tourists to choose their intended location to make the tourism sector grow again after the impact of covid 19.Methods: Geolocation concept with harvesine algorithm formula.Result: The research results are the output of the Mapbox api implementation application in the form of a geographical map of the island of Lombok by displaying spatial data of tourism locations, as well as the paths traversed to reach the intended tourist sites accompanied by the distance and time needed to reach them. The level of user satisfaction with the applications built is 87,62%.Conclusion: This research results in user satisfaction in finding information, location, and paths that can be reached to tourist sites.